A systematic review of skills and techniques to improve patient-physician feedback - Soriano-Sánchez, José-Gabriel; Jiménez-Vázquez, David (Revista Acciones Médicas, 2022)
Currently, medical personnel require a wider range of skills to foster understanding and strengthen autonomy during their consultations. Innovative methods should be taught to enhance communication skills between physicians and patients, in order to enable them to jointly make decisions under certain circumstances. Therefore, the aim of the present work is to identify by means of a systematic review different techniques and communication skills for doctor-patient interpersonal improvement. A systematic review was carried out using the Scielo, Web of Science, PsycINFO and Scopus databases, and after applying the inclusion and exclusion criteria, nine articles were left for review. The results reveal certain techniques and skills for improving interpersonal communication between doctor-patient. In conclusion, it is relevant to train medical staff in communication skills. In this way, they could learn to recognize the patient's emotions and needs and favor reflection, which will be used for diagnostic purposes and improvement of treatment results.
Keywords: feedback; physician; patient; systematic review.